2008
DOI: 10.1002/ejic.200800512
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate‐Bridged Dimeric Copper(II) Complexes with Three‐Dimensional Network: Synthesis, Structure and DFT Studies

Abstract: The 1:1 reaction of the diacetyl monoxime‐2‐pyridyl hydrazone HL1 (1) and the pyridine‐2‐carboxaldehyde‐2‐imidazoline hydrazone hydrobromide HL2 (2) with copper(II) sulfate pentahydrate in methanol affords a series of new sulfate‐bridged dimeric copper(II) complexes, [CuII2(HL1)2(μ‐SO4)2]·4H2O (1a) and [CuII2(HL2)2(μ‐SO4)Br2]·2H2O (2a), respectively. The room temperature magnetic moments of the complexes 1a and 2a are 1.82 μβ and 1.84 μβ, respectively. The bands appearing in the UV region (200–340 nm) are char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…The single-crystal X-ray structural analysis revealed that 1 crystallized in the triclinic space group P-1, and the asymmetric unit consists of one Cu, one dps, one coordinated SO 2À 4 , one coordinated water, and two lattice waters. The Cu 2+ cation exhibits a slightly distorted square pyramidal geometry [22], contains the same μ-SO 2À 4 ligand, but the Cu 2+ cation located in a more distorted square-pyramidal geometry, and the Cu···Cu distance (4.555 Å) is shorter than that in 1. Copper complexes with sulfur-bridged bis-pyridine 3181…”
Section: Resultsmentioning
confidence: 97%
“…The single-crystal X-ray structural analysis revealed that 1 crystallized in the triclinic space group P-1, and the asymmetric unit consists of one Cu, one dps, one coordinated SO 2À 4 , one coordinated water, and two lattice waters. The Cu 2+ cation exhibits a slightly distorted square pyramidal geometry [22], contains the same μ-SO 2À 4 ligand, but the Cu 2+ cation located in a more distorted square-pyramidal geometry, and the Cu···Cu distance (4.555 Å) is shorter than that in 1. Copper complexes with sulfur-bridged bis-pyridine 3181…”
Section: Resultsmentioning
confidence: 97%
“…The angle aO1-Cu2-O2 in the dimeric complex is also larger than its experimental value by approximately 7 8. [38] The HOMO and LUMO orbitals of the three complexes are shown in Figure 8. The HOMO and LUMO of each complex are mostly concentrated on the aromatic p moiety of the ligand system.…”
Section: Homogeneous Systemsmentioning
confidence: 99%
“…29,30 2.4b Synthesis of [Fe III (HL) 2 ]Cl 3 , 1a: To a stirred methanolic solution of anhydrous iron(III) chloride (0⋅03 g, 0⋅2 mmol) was added a solution of HL, 1, (0⋅03 g, 0⋅4 mmol) in methanol (5 ml) and the resulting reddish-pink solution was stirred for 0⋅5 h. The solvent was evaporated by rotary evaporator and recrystallized from methanol. Yield.…”
Section: Syntheses Of Ligand and Complexesmentioning
confidence: 99%
“…The association constant (K ass ) of complexes can be estimated spectrophotometrically (figure 1) according to the (1), 29,31 where X represents the absorption intensity, X lim represents the absorption intensity at full complexation, C 0 is the initial concentration of the ligand, C H and C G are the corresponding concentrations of the ligand and metal ion during titration. The K ass (UV-Vis) was found to be (6⋅4865 ± 0⋅004) × 10 5 for 1a which was higher than 1b (K ass (UV-Vis) 1⋅1960 ± 0⋅002) × 10 5 ) at 298 K.…”
Section: Thermodynamics Of Bindingmentioning
confidence: 99%